Exploring circular economies in the built environment from a complex systems perspective: A systematic review and conceptual model at the city scale. (May 2022) - Rios, Fernanda Cruz; Panic, Sonia; Grau, David; Khanna, Vikas; Zapitelli, Joseph; Bilec, Melissa
Highlights: Participatory approaches are key to ethical circular economy interventions in cities. Economics and decision sciences are lacking from circular economy research. Behavioral and policy issues remain understudied in the recent literature. Abstract: As one of the globe's leading sectors for resource use and carbon emissions, the built environment could play a vital role in the circular economy (CE). This study aimed to understand and map the complex systems inherent to CE interventions in the built environment. We conducted a systematic literature review and thematic analysis to identify CE case studies in different cities around the globe that have considered systemic dimensions of CE and their interconnections and iterations. These include governmental, economic, environmental, technological, societal, and behavioral dimensions. The case studies informed a conceptual model that illustrates how CE functions in an urban setting. The model represents the interdependencies, flows, feedbacks, and unintended consequences that may result from the interaction between the CE research dimensions in cities. We hope to help policymakers, designers, and researchers to better understand how CE functions in urban settings, and to ethically design changes in the system to achieve circularity goals. The results suggest that meaningful stakeholder engagement is key to co-designing ethical CE interventions in the built environment. Finally, engaging disciplines like economics and decision sciences, and better understanding the role of public policies and human behavior are vital to future CE interventions in urban settings.